Attitude towards and utilization of health insurance in a metropolitan city: a cross-sectional study - Thampi, Jerome G.; Hadaye, Rujuta (International Journal Of Community Medicine And Public Health, 2019)
Background: Data on attitudes towards and utilization of health insurance in Mumbai is lacking. The aim of the study was to assess the level of awareness about health insurance, the factors influencing the decision to subscribe and the patterns of utilization of health insurance. Methods: 201 principal earning members of households belonging to the 25-45 years age group were interviewed in a community-based household survey in a conveniently selected ward in Mumbai with the help of a pretested, semi-structured interview schedule. Results: The level of awareness about health insurance was 65.3%. 33.8% of the respondents had utilized or subscribed to some form of health insurance. 27.9% had used Government health insurance while 13.4% had used private health insurance. 7.5% had access to both Government and private health insurance. Conclusions: A concerted effort is necessary to sensitize the public about health insurance with strategic use of sentiment regarding community risk pooling.